PENGARUH KUALITAS TIDUR, KONSENTRASI BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP KEMAMPUAN PEMAHAMAN KONSEP PESERTA DIDIK KELAS VIII - Khoirunnisa, Devi; Rakhmawati, Rosida; Nabila, Siti Ulfa (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to determine the effect of sleep quality, learning concentration, and critical thinking skills on the conceptual understanding of eighth-grade students at public junior high schools in the Terbanggi Besar subdistrict. This study is a non-experimental quantitative study analyzed using path analysis. The research instruments consisted of a sleep quality questionnaire, a learning concentration questionnaire, a critical thinking ability test, and a concept comprehension ability test. The results of the analysis showed that sleep quality did not have a direct effect on critical thinking ability because the sig value was greater than the significance level, namely 0.504>0.05. Learning concentration has a direct effect on critical thinking skills with a sig value of 0.032<0.05. Sleep quality has an effect on conceptual understanding skills with a value of 0.048<0.05. Study concentration does not affect conceptual understanding ability, with a significance value of 0.162>0.05. Critical thinking ability directly affects conceptual understanding ability, with a significance value of 0.000<0.05. In the next model, sleep quality indirectly affects conceptual understanding ability because the direct effect value is smaller than the indirect effect. Learning concentration also indirectly affects conceptual understanding ability through critical thinking ability because the direct effect value is smaller than the indirect effect. Based on the research results, it can be concluded that critical thinking ability is a key factor that plays a role in improving students’ conceptual understanding ability. Sleep quality and learning concentration not only have a direct effect but also contribute indirectly to conceptual understanding ability through critical thinking abilitcritical thinking ability because the direct effect value is smaller than the indirect effect